Utilization of crude and recombinant ELISAs for serodiagnosis of camel trypanosomosis in Sudan - Mossaad, Ehab; Salim, Bashir; Suganuma, Keisuke; Hassan, Mohammed A.; Davaasuren, Batdorj; Elamin, Elgailani A.; Bakhiet, Amel O.; Satti, Rawan A.; Xuan, Xuenan; Musinguzi, Simon Peter; Inouef, Noboru (Regional Studies and Reports, 2019)
This study was carried out to evaluate the application of CATT/T. evansi, crude and recombinant (TeGM6-4r) antigen ELISAs in the diagnosis of camel trypanosomosis caused by two trypanosome species, T. evansi and T. vivax, in Sudan. Concurrently, the current situation of camel trypanosomosis was investigated based on the results of a serological analysis. The recombinant tandem repeat antigen TeGM6-4r is conserved among salivarian trypanosome species and was highly sensitive in the detection Trypanozoon, and T. vivax. It has been validated in the diagnosis of surra in cattle and water buffalo but not in camels. A comparative evaluation of a crude antigen ELISA and a recombinant antigen GM6 (rTeGM6-4r) ELISA was performed using 189 blood samples, which included 148 samples obtained from different camel herds in Eastern Sudan and 41 samples from camels that had been brought from Western Sudan to local markets. The results showed that the rTeGM6-4r ELISA detected the greatest number of positive samples (n=118, 62%), while CATT/T. evansi and the crude antigen ELISA detected the lowest number of positive samples (n=73, 39%). The kappa value of rTeGM6-4r as compared to TeCA ELISA was 0.5515, which indicated moderate agreement. We concluded that the rTeGM6-4r ELISA is the test of choice for use in screening camel for trypanosomosis caused by T. evansi and T. vivax in Sudan.
Keywords: Dromedary camels; ELISA; Serodiagnosis; Surra; Trypanosomosis